PENERAPAN PENDEKATAN MODIFIKASI-APOS TERHADAP KEMAMPUAN KOMUNIKASI PESERTA DIDIK KELAS VIII SMPN 13 PADANG - Herawati, Feri (Departemen Matematika, 2024)
This study aims to determine effect of the Modified-APOS (Action, Process, Object, Schema) approach in improving student’s mathematical communication skills. The research was conducted at SMP Negeri 13 Padang with a total sampleof 63 students in class VIII in the 2023/2024 academic year. The sample was devided into two classes, the experimental class and the control class. The process for choosing sample classes was carried out utilizing the Simple Random Sampling approach. The type of research conducted is Quasy Experiment research. As for research design used Nonequivalent Posttest-Only Control Group Design. The intrument used to collect data was a communication ability test consisting of 3 essay. The data obtained were analyzed for normality with Anderson-Darling test, homogenity of variance test with F-test and hypothesis testing with t-test. From the result of the study, the data obtained were normal and had homogenous variance. For hypothesis testing, p-value = 0,005 was obtained, which means that there is an effect of the M-APOS approach on student’s mathematical communication skills.Keywords — APOS approach, mathematical communication, modified-APOS